Funciones ejecutivas, personalidad y estilos de respuesta en el contexto penitenciario (2020)
A review of articles that deal with the issues about executive functions, personality and response styles (dissimulation) in the penitentiary field is carried out, to focus on the terms mentioned there from an integrative perspective. This, because the mind, cognitive processes and executive functions are the fundamental basis for a person's personality to be constituted as what we know daily as attitudes and behaviors, which can possibly lead people to take decisions or establish patterns of behavior according to a specific purpose. This review will try to ensure that the Terms that are defined provide clarity and motivation to continue with the revision of the topic, which has been little explored, establishing the possible relationship between them, taking into account the prison context.